Reducing negative attitudes toward older adults and increasing advocacy for policies to support older adults: Bayesian analysis approach - Yuho Shimizu; Takaaki Hashimoto; Kaori Karasawa (Acta Psychologica, 2023)
As the world's population is aging, it is necessary to create societies in which older adults and young people can live together comfortably. Reducing young people's negative attitudes toward older adults is a pressing issue. Given the unique characteristics of older adults, which most people will eventually become, we focused on how long people believe it will be before they become older adults (i.e., the subjective time of becoming older). To examine our hypotheses, we performed a Bayesian analysis, which has attracted considerable attention in psychological research in recent years. In Studies 1 and 2, even after controlling for variables such as youth identity and aging anxiety, those with a longer subjective time of becoming older had more negative attitudes toward older adults and lower advocacy for policies to support older adults. In Study 3, we examined the effect of shortening the participants' subjective time of becoming older by presenting an explanatory text on the stereotype embodiment theory and several related empirical findings. We observed decreased negative attitudes toward both the young-old and old-old groups and increased advocacy for policies to support older adults. In the supplemental experiment, the experimental manipulation used in Study 3 reduced participants' aging anxiety. Future studies should elaborate on the negative attitudes toward a broad subgroup of older adults, and examine the perceived relative importance of policies to support older adults compared with policies in other areas.